JURUS TANPA BENTUK DAN PENDEKAR TANPA NAMA KARYA SENO GUMIRA AJIDARMA - Erlis Nur Mujiningsih (LITERASI: Indonesian Journal of Humanities, 2014)
This paper discusses a novel entitled Nagabumi by Seno Gumira Ajidarma. This novel can be classified as a martial arts story with some characteristics of warrior characters, fighting and martial arts moves. Other characteristics are exposed in detail up to two volumes, each consisting of 762 pages. As with other martial arts story, this work has a background of historical events. A difference with other martial arts stories is that Nagabumi novel consists of two thick volumes, other martial stories are composed by several thin volumes. The story of Nagabumi novel flows from beginning to end. Read volume two should read the first volume. Another difference is that the main character tries to criticize the motto "in the sky there is upper sky". The main character, Nameless warrior is a mighty person and has a poweful move, formless move. Almost all wariors can be defeated He became number one, but to lose as the time goes with his growing age. Against time, there are no most mighty warrior. Keywords: martial arts stories, moves, novel, warrior, history